2017
DOI: 10.21608/zvjz.2017.7686
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Shiga Toxin – Producing Escherichia coli in Raw and Pasteurized Milk

Abstract: One hundred random samples of raw buffalo and pasteurized cow milk (50, each) were collected from different localities of Sharkia Governorate for the detection of E. coli. The isolates were screened by PCR for virulence associated genes as well as antibiotic sensitivity test to determine the most effective antimicrobial agent. Furthermore, an experimental study was carried out to detect the influence of pasteurization and processing of kariesh cheese and yoghurt on E. coli O 111 :H 8 inoculated in milk with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Along with this, the intrinsic microbiota of raw milk together with the starter cultures are expected to outcompete pathogens by lowering the pH (Baylis, 2009). Nevertheless, raw milk cheeses of different varieties (soft and semi-hard) have been described as sources of contamination or outbreaks of STEC, since they do not undergo pasteurisation and the production process is not effective in counteracting the proliferation of these bacteria (Schlesser et al, 2006;Caro and García-Armesto, 2007;Miszczycha et al, 2013Miszczycha et al, , 2016Peng et al, 2013;Ahmed and Samer, 2017;Celikl et al, 2021). However, STEC have been isolated from pasteurised milk cheese as well, possibly due to crosscontamination (Fereydouni and Darbouy, 2015;Callon et al, 2016;Cardoso and Marin, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with this, the intrinsic microbiota of raw milk together with the starter cultures are expected to outcompete pathogens by lowering the pH (Baylis, 2009). Nevertheless, raw milk cheeses of different varieties (soft and semi-hard) have been described as sources of contamination or outbreaks of STEC, since they do not undergo pasteurisation and the production process is not effective in counteracting the proliferation of these bacteria (Schlesser et al, 2006;Caro and García-Armesto, 2007;Miszczycha et al, 2013Miszczycha et al, , 2016Peng et al, 2013;Ahmed and Samer, 2017;Celikl et al, 2021). However, STEC have been isolated from pasteurised milk cheese as well, possibly due to crosscontamination (Fereydouni and Darbouy, 2015;Callon et al, 2016;Cardoso and Marin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These outbreaks, as reported by the data collected in the European Union One-Health (2022) report, demonstrate as raw milk cheese and other dairy products are frequently associated to the presence of STEC (2% of analysed dairy products (EFSA and ECDC, 2022)). Thus, in the absence of an effective pasteurisation process, the cheese production and ripening steps have proven to be insufficient to achieve the complete inactivation of these pathogenic E. coli microorganism (Bellio et al, 2018;Ioanna et al, 2018), as shown in studies that investigated the persistence of STEC in raw milk and its derivatives (Miszczycha et al, 2013;Peng et al, 2013;Ahmed and Samer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The serogroups of 12 representative E. coli isolates which were categorized as O111,O128, O91, and untyped E. coli strains (2 strain each), O26(3 strains), O44 (1 strain) as displayed in Table 4.These findings agreed with Momtaz et al [57]who reported that O26, O111, O91 O128 and O145 serogroups are the most frequent E. coli O-serogroups detected in raw cow's milk. Additionally, Ahmed and Samer [58] reported that E. coliO26, O44, and O111serogroups were identified from raw buffalo's milk samples in Egypt. Ranjbar et al [59] found that O26, O111, and O121serogroups were prevalent in STEC strains detected in raw milk and milk products in Iran.…”
Section: Moreovermentioning
confidence: 99%
“…On the other hand, Ahmed and Samer [58] proved that E. coli isolates were sensitive to gentamicin, ciprofloxacin and colistin. In China, all E. coli strains were susceptible to gentamicin and exhibited different resistance levels to ampicillin, amoxicillin-clavulanic acid, trimethoprim-sulfamethoxazole, tetracycline, and ciprofloxacin as (46.3%), (16.4%), (13.4%), (13.4%), and (1.5%), respectively [53].…”
Section: Unwisementioning
confidence: 99%